2015
DOI: 10.1213/xaa.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Platelet Transfusions and Desmopressin on Intracranial Bleeding in a Patient Receiving Ticagrelor

Abstract: We describe a case of a 67-year-old man who required emergency surgery for acute intracranial bleeding after having received a loading dose of aspirin and ticagrelor for an acute ST-elevation myocardial infarction. Before and during the craniocervical decompression, the assessment of platelet function was performed using the Multiplate® analyzer. Biological evaluation of platelet function was consistent with the clinical impression, suggesting that platelet transfusion and desmopressin administration in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Moreover, the plasma concentrations of both ticagrelor and its active metabolite remain much higher (5.2-fold and 7.7-fold, respectively) than the concentration required to induce half the maximum platelet effect (EC50) for at least 24 h [4]. This observation is consistent with recent clinical observations that we and others described recently reporting biological and clinical inefficacy of platelet transfusions in ticagrelor-treated patients with life-threating bleeding [29,30]. Studies based on multiple electrode aggregometry testing on whole blood showed that even a high dose of non-inhibited platelets had a limited effect in restoring platelet reactivity to ADP in patients treated with ticagrelor compared with clopidogrel [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the plasma concentrations of both ticagrelor and its active metabolite remain much higher (5.2-fold and 7.7-fold, respectively) than the concentration required to induce half the maximum platelet effect (EC50) for at least 24 h [4]. This observation is consistent with recent clinical observations that we and others described recently reporting biological and clinical inefficacy of platelet transfusions in ticagrelor-treated patients with life-threating bleeding [29,30]. Studies based on multiple electrode aggregometry testing on whole blood showed that even a high dose of non-inhibited platelets had a limited effect in restoring platelet reactivity to ADP in patients treated with ticagrelor compared with clopidogrel [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings provide a mechanistic explanation for the failure of transfusion to adequately restore platelet function in ticagrelor‐treated patients, as highlighted in two recent case reports , and confirm and extend similar observations by others . These preceding studies, however, examined healthy donor samples spiked with ticagrelor , or platelets from patients receiving loading doses of P2Y12 inhibitors , or a combined patient pool that received either loading or maintenance doses of ticagrelor or prasugrel 6–24 h prior to blood sampling .…”
Section: Discussionsupporting
confidence: 89%
“…Although the authors observed a partial restoration of platelet aggregation in patients on maintenance treatment with these drugs, other studies and case reports provided conflicting data. 6,7,[9][10][11] The complete inefficacy of platelet transfusions to reverse the antiplatelet action of ticagrelor was nicely highlighted in a case report of a patient with intracranial hemorrhage, where platelet reactivity levels remained virtually unchanged despite transfusion of 17 U of platelets. 7 Other reports provided similar results.…”
Section: Sibbing and Massberg Restoring Platelet Function On Antiplatmentioning
confidence: 99%
“…As long as this is not the case, we have to take the data coming from (in vitro) studies such as APTITUDE 5 and others [6][7][8][9][10] as the best available evidence for guidance of patient treatment. Second, the comparatively low sample size for prasugrel-treated patients (n=6) and ticagrelor-treated patients (n=3) in the APTITUDE-CABG cohort precludes from drawing definite conclusions on the feasibility of immediate and sustained platelet restoration after platelet transfusion with these 2 agents.…”
Section: Sibbing and Massberg Restoring Platelet Function On Antiplatmentioning
confidence: 99%
See 1 more Smart Citation